Different nanofluids effect on bubble characteristics at the isothermal bubble column. (25th March 2021) - Dousti, Ahmad; Gharedaghi, Hamed; Hanafizadeh, Pedram; Ashjaee, Mehdi
Abstract: In this study, the effect of different nanofluids such as SiO2, Fe3 O4, and Al2 O3 on bubble characteristics is studied experimentally. The nanoparticles concentration for the SiO2 nanofluid is 0.05 wt% and for other nanofluids is 0.005 wt%. Bubbles are formed by injection of air at a constant gas flow rate (between 600‐1200 mL/h) into a stagnant isothermal liquid column. Experimental data of formation, growth, and detachment of the air bubbles were recorded by a high‐speed digital camera (1200 fps), and the image processing method was used to analyze the bubble characteristics. In the present study, bubble characteristics such as diameter, size, aspect ratio, and detachment frequency were studied in four different liquids. The results show that a bubble has the biggest size in the pure water and adding nanoparticles to the pure water decreases bubble size. Also, the variation of detachment frequency has an inverse relation with the bubble size behaviour. Between different nanoparticles, Fe3 O4 has maximum and SiO2 has minimum effect on bubble features. By adding Fe3 O4 to pure water, bubble diameter decreases nearly 7%‐8% and bubble detachment frequency increases nearly 15%‐20%. In order to analyze the variation of the bubble characteristics, a force modelling on bubbles during the growth was proposed. Moreover, a correlation has been proposed for the prediction of bubble diameter at detachment time in three different nanofluids and in the pure water. The mean absolute error of this correlation is 2.65% and has a good agreement with experimental results.